Color rendering of art paintings under CIE illuminants for normal and color deficient observers - Linhares, João M. M. (2009)
Color rendering indices are used to access the quality of lighting but, in addition to other well-known limitations, are not defined for color deficient observers. We evaluated the quality of lighting for normal and color deficient observers in the context of art paintings by estimating the number of colors they perceive when looking at the paintings. Hyperspectral data from 11 oil paintings were analyzed to compute the number of discernible colors when the paintings were assumed rendered under 55 CIE illuminants. Models of color perception for normal and color deficient observers were applied in the estimates. It was found that the number of discernible colors for normal and color deficient observers had low correlation with traditional color rendering indices and that some three-band illuminants, like HP4, were found to be good for most cases, except for tritanopes.These results suggest that it may be possible to obtain good lighting conditions for normal and color ficient observers with an appropriate choice of the light source.